Cleaning efficiency of feed production lines after production of feedstuffs with coccidiostats. Issue 1 (October 2021) - Jankovic, S; Radicevic, T; Stefanovic, S; Tankovic, S; Djinovic-Stojanovic, J; Spiric, D; Nikolic, D
Abstract: Intensive broiler production implies regular use of coccidiostats approved as feed additives. However, due to their chemical properties, coccidiostats can stay behind in the production line, and consequently, unavoidable cross-contamination of non-medicated feedstuffs can result in the exposure of non-target animal species and in the potential for coccidiostat residues in foods, such as chicken meat and eggs, derived from these species. In this way, coccidiostats enter the human food chain and can pose a health problem. The aim of this study was to determine the success of line cleaning after the application of salinomycin and maduramicin in feed. We tested the cleaning matrix (wheat groats) in order to demonstrate how many cleaning replicates are needed to safely produce coccidiostat-free feedstuffs. After the application of salinomycin, it is recommended that, for safety reasons, the line be cleaned with at least five batches of wheat groats of 480 kg each. In the case of maduramicin, it is recommended the line be cleaned with a minimum of eight batches, considering the relatively low permissible level of maduramicin as a contaminant in medication-free feed.